Judicial Independence in Croatia Under European Scrutiny: Analysis of the Ruling Hann-Invest and Others (Or How to Save Judges from Other Judges) - Sanz-Caballero, Susana (Review of European and Comparative Law, 2025)
This contribution analyses the first case presented to the Court of Justice of the EU that questions the independence of the judiciary in Croatia. The case has several unique aspects. First, it addresses threats to judicial independence from within the judiciary itself, which is unusual, as most cases typically involve external pressures from the executive or legislative branches. Second, while the judicial practice under scrutiny was deemed contrary to EU law, interestingly the Court explained to Croatian authorities how they could rectify the situation. Third, the Advocate General’s Conclusions largely diverge from the Court’s ruling. While this is not so uncommon, it proves that this was not an easy case. Last, the case challenges and ultimately deems unjust a judicial practice that persists in Croatia as a remnant of the country’s communist past and which draws inspiration from an era when judges were subject to a strict judicial hierarchy to the detriment of their own autonomous opinion. The paper delves into the specifics of the Croatian case. It compares the legal reasoning of the Advocate General and that the Court of Justice, illustrating their differing approaches. The contribution explores other arguments that were not raised in the Conclusions that, interestingly, were included in the Court’s judgement. The Court ruled that Croatia’s practice – where a registrar judge, not involved in the case, could override a decision made by the court handling the case, and where an extended section of the court could also force the judges handling the case to give up their legal reasoning before they could even rule on the case – was incompatible with Article 19 TEU.